Cambridge community Optometry Glaucoma Scheme. (23rd September 2014) - Keenan, Jonathan; Shahid, Humma; Bourne, Rupert R; White, Andrew J; Martin, Keith R
Abstract Background With a higher life expectancy, there is an increased demand for hospital glaucoma services in the United Kingdom. Design The Cambridge community Optometry Glaucoma Scheme (COGS) was initiated in 2010, where new referrals for suspected glaucoma are evaluated by community optometrists with a special interest in glaucoma, with virtual electronic review and validation by a consultant ophthalmologist with special interest in glaucoma. Participants 1733 patients were evaluated by this scheme between 2010 and 2013. Methods Clinical assessment is performed by the optometrist at a remote site. Goldmann applanation tonometry, pachymetry, monoscopic colour optic disc photographs and automated Humphrey visual field testing are performed. A clinical decision is made as to whether a patient has glaucoma or is a suspect, and referred on or discharged as a false positive referral. The clinical findings, optic disc photographs and visual field test results are transmitted electronically for virtual review by a consultant ophthalmologist. Main Outcome Measures The number of false positive referrals from initial referral into the scheme. Results Of the patients, 46.6% were discharged at assessment and a further 5.7% were discharged following virtual review. Of the patients initially discharged, 2.8% were recalled following virtual review. Following assessment at the hospital, a further 10.5% were discharged after a single visit. Conclusions The COGS community‐based glaucoma screening programme is a safe and effective way of evaluating glaucoma referrals in the community and reducing false‐positive referrals for glaucoma into the hospital system.